KONTRAK PEMBIAYAAN MURABAHAH DAN MUSAWAMAH - Ilyas, Rahmad (Universitas Islam Negeri Sunan Kudus, 2015)
Islamic bank is a financial intermediary (Intermediary FinancialInstitution) whose operations are free from elements that are forbiddenby Islam, namely gambling, Gharar, Riba, Ryswah, and falsehood.thus different from conventional banks whose. operations using theprinciples of interest by most scholars say the same as usury. Theelement that distinguishes Islamic bank with a conventional bank is thenecessity of Shariah Supervisory Board (DPS) under the auspices of theNational Sharia Council of the Indonesian Ulema Council (DSN-MUI).Shariah Supervisory Board (DPS) is to monitor the operation of thebank and the products it releases in order to remain in accordance withthe provisions of Shari’ah. Murabaha is a contract of sale of goods bythe price of the goods plus an agreed profit margin. Based on the bank’ssale and purchase agreement to buy the goods ordered by and sold tocustomers. Bank selling price is the purchase price of the supplier plusan agreed profit.